THE EFFECT OF FEEDING FERMENTED PINNEAPLE SKIN IN THE DIET ON CARCASS PRIMAL CUTS AND FAT DISTRIBUTION IN PEKING DUCK - I. R., Putra; Ariana, I N. T.; Siti, N. W. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aimed to determine the effect of fermented pineapple skin in the diet on the primal carcass cut and fat distribution of 10-week-old Peking duck. This research was conducted from January to March 2021 at the Teaching Farm of the Faculty of Animal Husbandry, University of Mataram and continued at the Laboratory of Animal Products Processing Technology, Faculty of Animal Husbandry, University of Mataram, for three months. This study used a completely randomized design, which consisted of 3 treatments and 5 replications where each replication contained 2 peking ducks aged two weeks as many as 30 tails with homogeneous weight. The treatments were P0 = control, P1 = 10% fermented pineapple peel and P2 = 20% fermented pineapple peel. The variables observed were the percentage of chest, wings, thighs, back, mesentery fat percentage, gallbladder fat, cushion fat and abdominal fat. The results showed that the administration of 10% and 20 fermented pineapple peels could significantly reduce the percentage of bearing fat (P<0.05),  but the results showed no significant difference (P>0.05) on the percentage of chest, wings, back, thighs, mesentery fat percentage, gallbladder fat and abdominal fat. Based on the results of the study, it can be concluded that giving fermented pineapple peel to a level of 20%, reduced the percentage of cushioning fat but gave the same results on the percentage of chest, wings, back, thighs, mesentery fat percentage, gallbladder fat and abdominal fat. Key words: Peking duck, fermented pineapple skin, carcass primal cut, fat distribution